The Effect of Brinase on Fibrinogen in Vivo - Nyman, D (Thrombosis and Haemostasis, 1975)
Brinase infusions in man cause, without excessive lowering of the inhibitor capacity, a slowing of the fibrin polymerization. This is combined with a degradation of the A α chain into two major fragments. Both fragments carry crosslinking sites. Brinase infusion also causes positive ethanol gelation. Evidence for the formation of γ dimers was found.